2022
DOI: 10.3389/fpubh.2022.847161
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Public Sentiment in Major Public Emergencies Through the Complex Networks Method: A Case Study of COVID-19 Epidemic

Abstract: The main purpose of this study is to investigate what topic indicators correlate with public sentiment during “coronavirus disease 2019 (COVID-19) epidemic” and which indicators control the complex networks of the topic indicators. We obtained 68,098 Weibo, categorized them into 11 topic indicators, and grouped these indicators into three dimensions. Then, we constructed the complex networks model of Weibo's topics and examined the key indicators affecting the public's sentiment during the major public emergen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…Cheng et al [10] found that secondary disasters of major emergencies can have an impact on international oil prices. Yang et al [11] concluded that major emergencies can seriously affect the public's emotions and cause a certain amount of panic. Similarly, De las Heras-Pedrosa et al [12] argued that major emergencies can also have serious psychological effects on the public.…”
Section: Related Workmentioning
confidence: 99%
“…Cheng et al [10] found that secondary disasters of major emergencies can have an impact on international oil prices. Yang et al [11] concluded that major emergencies can seriously affect the public's emotions and cause a certain amount of panic. Similarly, De las Heras-Pedrosa et al [12] argued that major emergencies can also have serious psychological effects on the public.…”
Section: Related Workmentioning
confidence: 99%